Image guided brachytherapy in locally advanced cervical cancer: Improved pelvic control and survival in RetroEMBRACE, a multicenter cohort study. Issue 3 (September 2016) - Sturdza, Alina; Pötter, Richard; Fokdal, Lars Ulrik; Haie-Meder, Christine; Tan, Li Tee; Mazeron, Renaud; Petric, Primoz; Šegedin, Barbara; Jurgenliemk-Schulz, Ina Maria; Nomden, Christel; Gillham, Charles; McArdle, Orla; et al.
Abstract: Purpose: Image guided brachytherapy (IGBT) for locally advanced cervical cancer allows dose escalation to the high-risk clinical target volume (HRCTV) while sparing organs at risk (OAR). This is the first comprehensive report on clinical outcome in a large multi-institutional cohort. Patients and methods: From twelve centres 731 patients, treated with definitive EBRT ± concurrent chemotherapy followed by IGBT, were analysed. Kaplan–Meier estimates at 3/5 years were calculated for local control (LC, primary endpoint), pelvic control (PC), overall survival (OS), cancer specific survival (CSS). In 610 patients, G3–4 late toxicity (CTCAEv3.0) was reported. Results: Median follow up was 43 months, percent of patients per FIGO stage IA/IB/IIA 22.8%, IIB 50.4%, IIIA–IVB 26.8%. 84.8% had squamous cell carcinomas; 40.5% lymph node involvement. Mean EBRT dose was 46 ± 2.5 Gy; 77.4% received concurrent chemotherapy. Mean D90 HRCTV was 87 ± 15 Gy (EQD210 ), mean D2cc was: bladder 81 ± 22 Gy, rectum 64 ± 9 Gy, sigmoid 66 ± 10 Gy and bowel 64 ± 9 Gy (all EQD23 ). The 3/5-year actuarial LC, PC, CSS, OS were 91%/89%, 87%/84%, 79%/73%, 74%/65%. Actuarial LC at 3/5 years for IB, IIB, IIIB was 98%/98%, 93%/91%, 79%/75%. Actuarial PC at 3/5 years for IB, IIB, IIIB was 96%/96%, 89%/87%, 73%/67%. Actuarial 5-year G3–G5 morbidity was 5%, 7%, 5% for bladder, gastrointestinal tract, vagina. Conclusion: IGBT combined with radio-chemotherapy leads to excellent LC (91%), PC (87%), OS (74%), CSS (79%) with limited severe morbidity.